Convective heat transfer in diverging and converging microchannels. (January 2015) - Duryodhan, V.S.; Singh, Abhimanyu; Singh, S.G.; Agrawal, Amit
Abstract: In this work, experimental and three-dimensional numerical study is performed on single phase liquid flow in two scenarios: heated diverging and heated converging microchannel. Microchannel with 8° angle of divergence and 156 μm of hydraulic diameter is employed for experiments in both diverging and converging modes. The objectives are to obtain the Nusselt number and to understand the conjugate effect in varying cross-section microchannels with the viewpoint of using such geometries in the design of heat sinks for electronics cooling. The experiments are performed for mass flux and heat flux range of 113–1200 kg/m 2 -s ( Re  = 30–274) and 0.3–9.5 W/cm 2, respectively, with de-ionized water as the working fluid. The surface and bulk mean temperatures are measured, and used to calculate the heat transfer coefficient. Numerical results show that the conjugate effect results in different nature of heat flux distribution in diverging vs. converging microchannel. This leads to a nearly constant heat flux condition and 35% higher heat transfer in converging microchannel compared with diverging microchannel. It is further observed that less pumping work is required in diverging and converging microchannels as compared with uniform cross-section microchannel. The thermo-hydraulic performance of diverging and converging microchannels is of significance in the development of compact heat sinks.